Two-dimensional simulation of grain structure growth within selective laser melted AA-2024 - López Botello, Omar Eduardo; Martínez Hernández, Uriel; Ramírez, José; Pinna, Christophe; Mumtaz, Kamran (2016)
ABSTRACT: A two-dimensional Cellular Automata (CA) – Finite Element (FE) (CA-FE) coupled model has been developed to predict the microstructures formed during the laser melting of a powdered AA-2024 feedstock using the Additive Manufacturing (AM) process Selective Laser Melting (SLM). The presented CA model is coupled with a thermal FE model, which computes the heat flow characteristics of the SLM process. The developed model considers the powder-to-liquid-to-solid transformation, tracks the interaction between several melt pools within a melted track, and several tracks within various layers. It was found that the calculated temperature profiles as well as the simulated microstructures bared close resemblance with SLM fabricated AA-2024 samples. The developed model was capable of predicting melt pool cooling and solidification rates, the type of microstructure obtained, the size of the melt pool (with 14% error) and the heat affected zone, average grain size number (with 12% error) and the growth competition present in microstructures of components manufactured via SLM.